Implementation of Pro-Environmental-Based Teaching Materials to Improve Learning Outcomes and Behavior on Global Warming - Habibah, Habibah; Syam, Muliati; Komariyah, Laili (Universitas Lambung Mangkurat, 2025)
One problem in the school environment is the lack of information to improve attitudes that reflect environmental concerns. There is a need for methods to improve student's learning outcomes and pro-environmental behavior. This research aims to determine whether there is an increase in applying pro-environmental teaching materials to the educational objectives and behavior of high school students in Samarinda. This study used a pretest-posttest design with a single group and a quantitative methodology. Thirty-four people were selected for the sample using the purposive sampling technique. The data-gathering method includes questionnaires about environmental care behavior on global warming material, essays, and multiple-choice tests. The research was implemented over five class sessions using pro-environmental teaching materials developed by Anwar (2023), which included group discussions and interactive activities to raise awareness of global warming. Students' progress was assessed through regular observations and post-discussion evaluations. According to the study, student learning outcomes improved from 45.48 on the pretest to 77.79 on the post-test, resulting in a 0.57 rise in N-Gain and a moderate classification. Additionally, environmental care behavior enhanced from 44.85% on the pretest to 88.23% on the post-test, earning it a moderate classification with a 0.39 rise in N-Gain. As a result, the high school students in Samarinda demonstrated a considerable improvement in both behavior and learning outcomes when pro-environmental instructional materials were used. The study results can be used to improve the curriculum's ability to promote environmentally conscious behavior and awareness through development and adaptation. In summary, using pro-environmental instructional materials greatly enhances students' pro-environmental behavior and learning results in the context of global warming content.